2017
DOI: 10.18203/2319-2003.ijbcp20175691
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitudes on personal drug selection exercise in writing prescription

Abstract: INTRODUCTIONPharmacology, the study of drugs, is mainly taught to 3 rd , 4 th and 5 th semester medical students in India. The traditional pharmacology teaching mainly takes place through didactic lectures, in which passive transfer and memorizing of information of drug class and individual compounds occurs. Whereas practical curriculum mainly includes pharmacy practical, animal experimentations, prescription writing and problem based learning (PBL) which has been criticized. So, there is a need to evaluate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…In this study among 132 medical students, 126 (95.45%) had a positive attitude on P-drug selection exercises which is similar to another study with a prevalence of 90%. 5 Another study reported the prevalence of positive attitude on p-drug selection with 74.9%. 9 , 10 P-drug practical is dynamically understood and perceived by medical undergraduates and also included in the university final practical exam, hence it is encouraged in our settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study among 132 medical students, 126 (95.45%) had a positive attitude on P-drug selection exercises which is similar to another study with a prevalence of 90%. 5 Another study reported the prevalence of positive attitude on p-drug selection with 74.9%. 9 , 10 P-drug practical is dynamically understood and perceived by medical undergraduates and also included in the university final practical exam, hence it is encouraged in our settings.…”
Section: Discussionmentioning
confidence: 99%
“… 3 - 5 It helps to guide educational interventions for P-drug selection exercises that can improve students' abilities to make well-informed, patientcentred decisions about medication therapy by identifying obstacles and knowledge gaps. 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher total score indicated a better value. 12 The drug with the highest score became the personal drug choice. Next step was to verify suitability for selected P drug for particular patient.…”
Section: Methodsmentioning
confidence: 99%